2013
DOI: 10.3762/bjnano.4.72
|View full text |Cite
|
Sign up to set email alerts
|

Ultramicrosensors based on transition metal hexacyanoferrates for scanning electrochemical microscopy

Abstract: SummaryWe report here a way for improving the stability of ultramicroelectrodes (UME) based on hexacyanoferrate-modified metals for the detection of hydrogen peroxide. The most stable sensors were obtained by electrochemical deposition of six layers of hexacyanoferrates (HCF), more specifically, an alternating pattern of three layers of Prussian Blue and three layers of Ni–HCF. The microelectrodes modified with mixed layers were continuously monitored in 1 mM hydrogen peroxide and proved to be stable for more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…However, the key question to be addressed was whether H2O2 can be detected as a product of the photoelectrocatalytic conversion. Since the molar concentrations of H2O2 accumulated in our cells were below the detection limit of the conventional colorimetric H2O2 determination using a reaction with titanium peroxo-complex, we measured the H2O2 evolution in-situ using amperometric microsensors [55][56][57]. To this end, we used H2O2 microelectrodes (diameter of 25 m) modified with Prussian blue (PB), as an effective electrocatalyst for H2O2 reduction, positioned approx.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the key question to be addressed was whether H2O2 can be detected as a product of the photoelectrocatalytic conversion. Since the molar concentrations of H2O2 accumulated in our cells were below the detection limit of the conventional colorimetric H2O2 determination using a reaction with titanium peroxo-complex, we measured the H2O2 evolution in-situ using amperometric microsensors [55][56][57]. To this end, we used H2O2 microelectrodes (diameter of 25 m) modified with Prussian blue (PB), as an effective electrocatalyst for H2O2 reduction, positioned approx.…”
Section: Resultsmentioning
confidence: 99%
“…Electrochemical deposition of PB on Pt microelectrodes (diam. 25 µm) was carried out according to previously published procedures [55][56][57]. In brief, four cycles in a potential range of 0.4 and 0.75 V vs. Ag/AgCl at a scan rate of 0.02 V/s were applied in a freshly prepared solution of 1.25 mM K3[Fe(CN)6] and 1.25 mM FeCl3 in 0.1 M HCl / 0.1 M KCl solution.…”
Section: H2o2 Detectionmentioning
confidence: 99%
“…Operando SECM operated in the SG-TC mode was employed to investigate substrate-generated H 2 O 2 by using a highly stable and selective ultramicrosensor (made of Prussian Blue modified with films of iron and nickel hexacyanoferrates) as a tip. A Au surface was biased to generate H 2 O 2 while the selective tip was employed for imaging the distribution of H 2 O 2 . The RC and SG-TC modes were also applied to investigate the electrochemical activities of various AuPd compositions deposited onto ITO toward H 2 O 2 and FcMeOH + reduction reactions .…”
Section: Operando Sepm Applications In Electrocatalysismentioning
confidence: 99%
“…A Au surface was biased to generate H 2 O 2 while the selective tip was employed for imaging the distribution of H 2 O 2 . 546 The RC and SG-TC modes were also applied to investigate the electrochemical activities of various AuPd compositions deposited onto ITO toward H 2 O 2 and FcMeOH + reduction reactions. 547 Tomlinson et al reported the first use of electrochemical imaging to identify the defect and defect-free areas in single crystal boron-doped diamond (BDD) electrodes.…”
Section: Operando Sepm Applications In Electrocatalysismentioning
confidence: 99%
“…Besides Prussian Blue (PB), which is indeed ferric hexacyanoferrate, deposits of different metal hexacyanoferrates (such as copper (II), cobalt (II), nickel (II), etc.) potentially can be also used as an electrocatalytic properties promoting material in development of chemical sensors and biosensors . However, the mechanism of hydrogen peroxide reduction catalysis by transition metals hexacyanoferrates is not discovered yet .…”
Section: Introductionmentioning
confidence: 99%